Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Relationships between leaf morphological traits, nutrient concentrations and isotopic signatures for Mediterranean woody plant species and communities - Domínguez, María T.; Aponte, Cristina; Pérez-Ramos, Ignacio M.; García, Luis V.; Villar, Rafael; Marañón, Teodoro (Plant and Soil, 2012)
Background and aims Soil factors are driving forces that influence spatial distribution and functional traits of plant species. We test whether two anchor morphological traits—leaf mass per area (LMA) and leaf dry matter content (LDMC)—are significantly related to a broad range of leaf nutrient concentrations in Mediterranean woody plant species. We also explore the main environmental filters (light availability, soil moisture and soil nutrients) that determine the patterns of these functional traits in a forest stand. Methods Four morphological and 19 chemical leaf traits (macronutrients and trace elements and δ 13 C and δ 15 N signatures) were analysed in 17 woody plant species. Community-weighted leaf traits were calculated for 57 plots within the forest. Links between LMA, LDMC and other leaf traits were analysed at the species and the community level using standardised major axis (SMA) regressions Results LMA and LDMC were significantly related to many leaf nutrient concentrations, but only when using abundance-weighted values at community level. Among-traits links were much weaker for the crossspecies analysis. Nitrogen isotopic signatures were useful to understand different resource-use strategies. Community-weighted LMA and LDMC were negatively related to light availability, contrary to what was expected. Conclusion Community leaf traits have parallel shifts along the environmental factors that determine the community assembly, even though they are weakly related across individual taxa. Light availability is the main environmental factor determining this convergence of the community leaf traits.
Keywords: Community weighted means; functional traits; isotopes; leaf dry matter content; Leaf mass per area; macronutrients; Specific leaf area

Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration. - Gómez-Aparicio, LORENA; Ibáñez, Beatriz; Serrano, María S.; De Vita, Paolo; Avila, José M.; Pérez-Ramos, Ignacio M.; García, Luis V.; Esperanza Sánchez, M.; Marañón, Teodoro (The New phytologist, 2012)
Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline. We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen species (Phytophthora cinnamomi, Pythium spiculum and Pythium spp.) as a function of local abiotic conditions (soil texture) and the characteristics of the tree and shrub neighborhoods (species composition, size and health status). The implications of pathogen abundance for tree seedling performance were explored by conducting a sowing experiment in the same locations in which pathogen abundance was quantified. Pathogen abundance in the forest soil was not randomly distributed, but exhibited spatially predictable patterns influenced by both abiotic and, particularly, biotic factors (tree and shrub species). Pathogen abundance reduced seedling emergence and survival, but not in all sites or tree species. Our findings suggest that heterogeneous spatial patterns of pathogen abundance at fine spatial scale can be important for the dynamics and restoration of declining Mediterranean forests.
The following values have no corresponding Zotero field: accession-num: 22428751
Keywords: Biological; Forest decline; Host-Pathogen Interactions; Mediterranean Region; Models; neighborhood models; Phytophthora; Phytophthora: physiology; Pythium; Pythium: physiology; Quercus; Quercus suber; Quercus: microbiology; regeneration dynamics; Seedling; Seedling: microbiology; Soil Microbiology; soil texture; soil-borne pathogens; species coexistence

Oak trees and soil interactions in Mediterranean forests: a positive feedback model - Aponte, Cristina; García, Luis V.; Pérez-Ramos, Ignacio M.; Gutiérrez, Eduardo; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the spectrum of variability of chemical elements in a Mediterranean forest ecosystem across the different compartments? Do coexisting tree species with different leaf chemical composition and nutrient cycling distinctly modify soil conditions? Could these species-speciﬁc, treegenerated soil changes create a potential positive feedback by affecting longterm species distribution? Location: Mixed oak forests of southern Spain, Los Alcornocales Natural Park. Methods: We sampled and chemically analysed ﬁve different ecosystem components: leaves, leaf fall, litter and superﬁcial (0–25 cm) and sub-superﬁcial (25–50 cm) soil beneath the canopies of evergreen Quercus suber and deciduous Q. canariensis trees. We used multiple co-inertia analysis (MCoA) to conjointly analyse the patterns of variability and covariation of eight macro- and micronutrients determined in each of the sampled ecological materials. We implemented a path analysis to investigate alternative causal models of relationships among the chemical properties of the different ecosystem components. Results: Variability in the concentration of chemical elements was related to the nature of their biogeochemical cycles. However, the rank of element concentration was consistent across ecosystem components. Analysis of coinertia (MCoA) revealed that there was a common underlying multivariate pattern of nutrient enrichment in the ecosystem, which supported the hypothesis of a separation in biogeochemical niches between the two co-existing oak species, with Q. canariensis having richer plant tissues and more fertile soil directly under each tree than Q. suber. The feasibility of a potential tree–soil positive feedback model was the only statistically validated among several alternative (non-feedback) models tested. Conclusions: In the studied Mediterranean forests, oak species distinctly modify soil fertility conditions through different nutrient return pathways. Further investigation is needed to address whether these tree-generated soil changes could affect seedling establishment and ultimately inﬂuence species distribution.
Keywords: Biogeochemical niche; ecological stoichiometry; ecosystem functioning; Foliar analysis; nutrient cycling; Quercus canariensis; Quercus suber; Soil fertility

Is selective thinning an adequate practice for adapting Quercus ilex coppices to climate change? - Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Joffre, Richard; Rambal, Serge (Annals of Forest Science, 2011)
& Introduction Future climatic scenarios demand an increasing involvement of management for forest preservation, but little is known on how forestry practices will benefit stands in facing variation of climatic components. & Objectives We investigated how selective thinning affected the response of an old Quercus ilex coppice to 6 years of throughfall reduction. Plots thinned from below (≈30% basal area removal) and unthinned plots were subject to either throughfall exclusion (TE; ≈33% throughfall reduction) or normal rainfall. Stem diameter growth, stem survival, and seed and sprout production were measured. & Results TE did not have a significant effect on stem growth but it reduced the production of viable acorns. Also, in the absence of thinning, TE accelerated the mortality of small stems and stimulated the emergence of new sprouts. Thinning reduced stem mortality, enhanced growth of residual stems, and caused a profuse emission of resprouts. Thinning also increased total seed production, but the crop had a large proportion of aborted seeds, especially in those areas subject to TE. & Conclusion The mere elimination of suppressed and diseased stems in abandoned Q. ilex coppice stands helps remaining trees to cope with current and future (probably longer and more intense) droughts. Potentially drier conditions might attenuate the success of thinning in producing a viable seed crop.
Keywords: Drought; forest adaptation strategy; seed production; sprouting; stem growth

Seed removal in two coexisting oak species: ecological consequences of seed size, plant cover and seed-drop timing - Pérez-Ramos, Ignacio M.; Urbieta, Itziar R.; Marañón, Teodoro; Zavala, M. A.; Kobe, Richard K. (Oikos, 2008)
Seed predation and dispersal can critically influence plant community structure and dynamics. Inter-specific differences arising at these early stages play a crucial role on tree recruitment patterns, which in turn could influence forest dynamics and species segregation in heterogeneous environments such as Mediterranean forests. We investigated removal rates from acorns set onto the ground in two coexisting Mediterranean oak species –Quercus canariensis and Q. suber– in southern Spain. We developed maximum likelihood estimators to investigate the main factors controlling probabilities of seed removal and to describe species-specific functional responses. To account for inter-specific differences in seed-drop timing, two experiments were established: a simultaneous exposure of acorns of the two species (synchronous experiments) and a seed exposure following their natural seed-drop phenology (diachronic experiments). A total of 1536 acorns were experimentally distributed along a wide and natural gradient of plant cover, and removal was periodically monitored for three months at two consecutive years (with contrasting differences in seed production and thus seed availability on the ground). The probability of seed removal increased with plant cover (leaf area index, LAI) for the two oak species. Inter-specific differences in acorn removal were higher in open areas and disappeared in closed microhabitats, especially during a non-mast year. Despite later seed-drop, Q. suber acorns were removed faster and at a higher proportion than those of Q. canariensis. The higher probability of seed removal for this species could be attributed to its larger seed size compared to Q. canariensis, as inter-specific differences were less pronounced when similar sized acorns were exposed. Inter-specific differences in seed removal, arising from seed size variability and microsite heterogeneity, could be of paramount importance in oak species niche separation, driving stand dynamics and composition along environmental gradients.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: plant cover (voyant); Quercus canariensis; Quercus suber; Seed removal; Seed size

Soil water content and emergence time control seedling establishment in three co-occurring Mediterranean oak species - Urbieta, Itziar R.; Pérez-Ramos, Ignacio M.; Zavala, Miguel A.; Marañón, Teodoro; Kobe, Richard K. (Canadian Journal of Forest Research, 2008)
Tree species can differ in their responses to resource availability during the critical phase of establishment, which could influence forest dynamics. In Mediterranean forests, most of the attention has focused on the effects of shade and summer drought on seedling survival, but little is known about the effect of autumn to spring rains on earlier stages of recruitment. A sowing experiment was set up along natural light and water gradients with three co-occurring oak species (Quercus suber L. (cork oak), Quercus canariensis Willd. (Algerian oak), and Quercus pyrenaica Willd. (Pyrenean oak)) that show limited natural regeneration in southern Spain. Recruitment stages were monitored for 1 year. Models of seed germination, seedling emergence, and seedling survival as well as of overall recruitment patterns were developed as functions of light, soil moisture, and soil compaction. The influence of intraspecific variation in seed mass and emergence time were also tested. Excess soil water levels during the winter reduced germination and emergence and lengthened time to emergence (in waterlogged open areas), which in turn decreased seedling survival during the dry season. Seedlings from larger seeds were more likely to germinate and emerge. The results suggest that temporal and spatial variability of soil water content, mediated by emergence time and seed size, play a crucial role in the regeneration dynamics of Mediterranean oak forests.
doi: 10.1139/X08-089doi: 10.1139/X08-089The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: Mediterranean oak species; Modelling; seed germination; seedling emergence; seedling survival (voyant); Soil water content